Review of Quedius (Coleoptera, Staphylinidae) described from the 1934 expedition by R. Malaise to Myanmar - Brunke, Adam James (European Journal of Taxonomy, 2023)
A taxonomic review was conducted of the type material of Quedius rove beetles (including Indoquedius, previously a subgenus) described by Otto Scheerpeltz from the 1934 Swedish expedition by René Malaise to Kambaiti, Myanmar. The specimens were mistakenly thought to be lost or compromised during the Second World War, and so the corresponding available names were not considered in the extensive taxonomic study of Quedius from the Himalayan Region and mainland China that has followed. This has resulted in the following synonyms: Indoquedius nonparallelus Zhao & Zhou, 2010 syn. nov. = I. malaisei (Scheerpeltz, 1965); I. baliyo Smetana, 1988 syn. nov. = I. micantiventris (Scheerpeltz, 1965); I. sanguinipennis (Scheerpeltz, 1965) syn. nov., I. bicoloris Smetana, 2014 syn. nov. = I. parallelicollis (Scheerpeltz, 1965); Quedius cornutus Cai et al., 2015 syn. nov. = Q. rutilipennis Scheerpeltz, 1965; Q. sundar Smetana, 1988 syn. nov., Q. hecato Smetana, 2012 syn. nov. = Q. semilaeviventris Scheerpeltz, 1965; Q. kambaitiensis Scheerpeltz, 1965 syn. nov. = Q. muscicola Cameron, 1932. The species collected by Malaise were treated within the most recent phylogenetic context, resulting in Malaisdius gen. nov., M. ruficeps (Scheerpeltz) comb. nov., and new or revised morphological concepts for the Apicicornis and Masasatoi species groups of Quedius (Microsaurus), and the Muscicola group of Quedius (Raphirus). Malaisdius smetanai gen. et sp. nov. is described from Nepal.